2008
DOI: 10.1590/s1415-47572008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Lack of mutations in the PVRL3 gene in North American caucasians with non-syndromic cleft lip/palate

Abstract: Cleft lip with or without cleft palate (CLP) is one of the most common birth defects. In about 70% of cases, CLP occurs as an isolated anomaly, denoted non-syndromic CLP (nsCLP). Genetic linkage and association studies have implicated many loci in susceptibility to nsCLP, including some members of the nectin gene family. We performed mutation screening of the PVRL3 gene that encodes nectin-3 in 73 unrelated Caucasian nsCLP patients and 105 unrelated controls from North America. We detected no sequence variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Early assumption that the selected NSCLP family had a lower copy number of PVRL3 compared to the normal individuals was not significantly proven. A normal detection of PVRL3 copy number in the NSCLP family reflected the finding by Sözen, Hecht, and Spritz (2008) that found no evidence of sequence variations in exons, intron, and noncoding sequences of PVRL3 among North American Caucasian population (Sözen et al, 2008). On contrary, other nectin-family paralogues, PVR, PVRL1, and PVRL2, have been identified as candidate genes and play a role in etiology of NSCLP via genome-wide linkage and association studies (Sözen et al, 2008;Warrington et al, 2006).…”
Section: Nonsignificant Copy Number Gain or Loss In Lphn2 And Pvrl3mentioning
confidence: 73%
“…Early assumption that the selected NSCLP family had a lower copy number of PVRL3 compared to the normal individuals was not significantly proven. A normal detection of PVRL3 copy number in the NSCLP family reflected the finding by Sözen, Hecht, and Spritz (2008) that found no evidence of sequence variations in exons, intron, and noncoding sequences of PVRL3 among North American Caucasian population (Sözen et al, 2008). On contrary, other nectin-family paralogues, PVR, PVRL1, and PVRL2, have been identified as candidate genes and play a role in etiology of NSCLP via genome-wide linkage and association studies (Sözen et al, 2008;Warrington et al, 2006).…”
Section: Nonsignificant Copy Number Gain or Loss In Lphn2 And Pvrl3mentioning
confidence: 73%
“…Suggestive linkage of LOD score in family 99 and HLOD ≥1 in total family for 3q13.3-13.33 chromosomal region brought to the interest of this study, with the findings of Poliovirus Receptor-Related 3 ( PVRL3 ) gene related to orofacial cleft. Sözen et al, [ 32 ] has screened several regions of coding exons, adjacent introns and noncoding sequences of PVRL3 and concluded that no variant mutations found in the selected regions in Caucasian polpulations. However, there is possibility that the variants were not detected by the SSCP/heteroduplex screening method used [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sözen et al, [ 32 ] has screened several regions of coding exons, adjacent introns and noncoding sequences of PVRL3 and concluded that no variant mutations found in the selected regions in Caucasian polpulations. However, there is possibility that the variants were not detected by the SSCP/heteroduplex screening method used [ 32 ]. Suggestive linkage at chromosomal locus 6p12.2 from family 58 harbor COL21A1 (alpha chain of type XX1 collagen) that have never reported associated with craniofacial development.…”
Section: Discussionmentioning
confidence: 99%